Translating in the Dark: Introspective Insights into the Work of the Blind and Low Vision Translators (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study aims at exploring and describing translation process (TP) as carried out by blind and low vision translators (BLVTs) compared to peer sighted translators (PSTs). The peculiarity of TP by the visually impaired has not been examined before in translation studies. For this end, we seek to find evidence for difference in processing texts between BLVTs and PSTs, impact of blindness and low vision on performing the task, and how such knowledge can help in structuring process-oriented model of translation assessment. Three hypotheses are proposed: first, there is a difference in performing the task in mainly three aspects; reciprocity, anxiety and speed between the visually impaired and the sighted translators; second, BLVTs tend to be more verbose in their translation; and third, a process-oriented model of translation along product-oriented model assessment can be a more impartial mechanism to assess performance of translation trainees as well as the final product. Introspective reports (2242 minutes of think-aloud audio recordings) are used to collect data from semi-professional translators (15 BLVTs and 10 PSTs). Triangulation is also used in form of pre-reports about the task and post-reports and interviews with the participants. The data are codified using multi-level bookmarking for recordings. The results show that BLVTs are slower, more anxious, and uncertain, more verbose, and self-reflective compared to PSTs. Further, BLVTs and PSTs have suffered from Hawthorne effect and have been optimistic about time of completion. Any contribution into this field can be useful in many ways, and future research can build on the findings of this study to provide better support to BLVTs in their work.
Keywords: Translation Process Research; Introspection in Translation; Blind and Low Vision; Translation Cognition; Think-Aloud Protocols